Truthmakers the contemporary debate - Beebee, Helen; Dodd, Julian (Oxford : Clarendon Press, 2010)
The concept of truthmaking is attracting much attention in contemporary metaphysics. This work asks how the truthmaker principle should be formulated, whether it is well motivated whether it genuinely has the explanatory roles claimed for it and whether more modest principles might serve just as well.
Earlier versions of papers were delivered at a conference held at the University of Manchester, May 2002.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Truth; Realism